Shaikh Azizur Rahman Nesarabadi's approaches, methods and thoughts in enhancing unity in diversity in Bangladesh - Huq, Fayzul (Kulliyyah of Islamic Revealed Knowledge and Human Science, International Islamic University Malaysia, 2019)
This study explores the contribution of Shaikh Azizur Rahman Nesarabadi (1915-2008) to the development of Islamic Unity and social harmony in Bangladesh through his intellectual and socio-political activities. This research critically evaluates his discourse on Ittehad Ma'al Ikhtelaf (Unity in diversity) in Bangladesh which has gained tremendous acceptance among the educated and common Muslim in Bangladesh since 1990s. This study is based on the investigation of Shaikh Nesarabadi's life, intellectual legacy, social activities and religious contributions. This research primarily applied a textual analysis method to examine the primary and secondary data. It is often stated that Muslims in Bangladesh are polarised and disunited. Even, the Islamist groups, who are supposed to be the symbol of Muslim Unity, are not out of this polarisation and disunity trend. More than hundreds Islamic groups in Bangladesh but unfortunately, there is no single platform. The research has shown that there are some seminal causes behind Muslim disunity, including fear of losing personal and group interest, party politics, questions of leadership, and a lack of proper approaches and methods. To retaliate and recalibrate these challenges and bridge the huge gaps between Islamist groups, the study found three practical solutions from Shaikh Nesarabadi's unity theory. According to Shaikh Nesarabadi, Muslims should focus on common issues, Tawhidic unity, and moderation and mutual respect. Therefore, the study concludes that Shaikh Nesarabadi's thought and theory on unity depend upon three elements: moderation and mutual respect focus on common interest, and finally the Tawhidic paradigm. These comprise the framework for Muslim unity, which must be adopted by Muslim political parties as well as individuals in order to fulfil the command of Allah to enable the Ummah to resume a leading role in the world as a champion of justice.